Android-based Application of Production Cost Calculation of Food and Beverage of the MSME - Ainuna Qurrata Ayunina; Sumarno Sumarno (Universitas Muhammadiyah Sidoarjo, 2022)
Determination of the cost of production is important for a product, many businesses determine the selling price that is not in accordance with the production cost that has been issued. Therefore, businesses have a desire to use a technology that is fast and appropriate to determine the cost of production. The purpose of making this application is to facilitate the process of determining the profit and selling price of an appropriate product based on the cost of production. The method used to calculate the cost of production is the full costing method. The app was created using the Kodular app inventor. With the making of this application can make it easier for MSME actors who have food or beverage products to calculate the basic price of production.